KARAKTERISASI GENETIK IKAN LELE DUMBO BERDASARKAN MARKER RAPD FINGERPRINTING - Estu Nugroho; Sabara Putera (BERITA BIOLOGI, 2018)
African catfish, namely lele dumbo, is an economically important fresh water fish in Nusa Tenggara Barat. There are three strains of African catfish that are well distributed among farmers. Genetic information of three strain catfish stocks is needed in order to sustain their development program. Genetic variations of the three strains of catfish, i.e. Sangkuriang, Masamo, Paiton has been evaluated using RAPD markers. DNA genome was extracted using phenol-chloroform methods. DNA was amplified using 20 primers (OPA 1 – 20). The results showed that three of the 20 primers have good amplification products. There was no significant genetic differences among three strains of catfish analyzed (P>0.05). Genetic variation of three African catfish stocks ranges from low to middle value. The highest genetic variation is found in strain Masamo with heterozygosity of 0.273 (with 70% polymorphism loci), followed by Sangkuriang 0.189 (60%) and Paiton 0.147 (40%). Hybrid candidates of Masamo-Sangkuriang have eterozygosity ranges between 0.256 - 0.306 (with 66.6 7 – 73.77% polymorphism loci). Strain Masamo and Paiton has more close genetic relationship than among the both and Sangkuriang.